A Model of the United Kingdom's Monetary Sector - Crouch, R. L. (Econometrica, 1967)
This paper estimates a model of the United Kingdom's monetary sector comprising supply and demand functions for various types of monetary assets including currency, bank reserves, demand deposits, time deposits, and total deposits. The model is closed by a simple distributed lag version of the quantity theory of money. Since the matrix of endogenous variables turns out to be triangular, the model is superficially recursive and thus OLS may be a consistent, FIML estimator of the system. In case the other conditions for recursiveness are not met and the system is genuinely interdependent, TSLS estimates are also presented. Various interest rates and income elasticities are calculated. They conform broadly with previous single equation estimates of their magnitude.